Aktivitas Dakwah Tuanku Tambusai dalam Proses Perkembangan dan Pembaharuan Islam di Daerah Rokan Hulu dan Sekitarnya Awal Abad ke-19 - Ginda Ginda (An-Nida', 2013)
especially in the aspects of activities da’wa and Islamic reform in Rokan Hulu and the surrounding area in the 19th century. As a national hero, heroic side against Holland has been a lot of attention, but the religious side very little studied. While the motives of resistance and struggle against the Dutch can not be separated from his perspective and clergy who see the Netherlands is unjust rulers to be suppressed. For her battle with the Dutch Tambusai. Propagation spirit and the struggle against the Dutch had brought him as the man